Reliability and validity of the instrument for scoring clinical outcomes of research for epidermolysis bullosa (iscorEB) - Bruckner, Anna L. (Br J Dermatol, 2018)
BACKGROUND: Epidermolysis bullosa (EB) is a group of rare and currently incurable genetic blistering disorders. As more pathogenic driven therapies are being developed, the need for EB-specific validated outcomes measures designed for use in clinical trials is becoming important. OBJECTIVES: We previously reported on development of an instrument for scoring clinical outcomes of research for Epidermolysis Bullosa (iscorEB), a new combined clinician and patient reported outcomes tool. We proceeded to test the reliability and construct validity of iscorEB in this study. METHODS: Observational study consisting of independent one-day assessments (6 assessors) at 2 academic hospitals. The assessments consisted of iscorEB clinician (iscorEB-c), Birmingham Epidermolysis Bullosa Severity (BEBS), and global severity assessment for physicians; and iscorEB patient (iscorEB-p), Quality of Life in Epidermolysis Bullosa (QOLEB) and Children’s Dermatology Life Quality Index (CDLQI) for patients. Construct validity and intra-class correlation coefficients (ICC) for inter-observer, intra-observer, and test-retest reliability were calculated. RESULTS: Thirty one patients with a mean age of 19.5 years (1.8–45.2) were included. Disease severity was mild in 42%, moderate in 29% and severe in 29% of cases. The inter-observer ICC was 0.96 for both the clinician-reported section of iscorEB-c and BEBS. The ICC for intra-observer reliability was 0.91 and 0.70 for the skin and mucosal domains of iscorEB-c, respectively. Cronbach’s alpha for iscorEB-c was 0.89. iscorEB-p’s test-retest reliability was 0.97, and Cronbach’s alpha was 0.84. The clinical score differentiated between subjects with mild, moderate and severe disease, and both clinical and patient subscores discriminated between recessive dystrophic EB and other EB subtypes. CONCLUSION: iscorEB has robust reliability and construct validity, including strong ability to distinguish EB types and severities. Further studies are planned to test its responsiveness to change.